Quo Vadis Pendidikan Indonesia: Kurikulum Berubah, Pendidikan Membaik? - Iik Jihan; Masduki Asbari; Siti Nurhafifah (AGUSPATI RESEARCH INSTITUTA, 2023)
The aim of character education is related to the mental formation and attitudes of students. However, if observed carefully, the main goal of character education can be said to have failed or not been achieved, this can be seen clearly from the results of the learning carried out by teaching staff for students as recipients of the lessons. This study report uses a descriptive qualitative method by taking notes because the data source was obtained by listening to oral narratives from the Bina Putera Institute's YouTube channel entitled